Extensor Mechanism Injury in the Pediatric Population—A Clinical Review - Sessions, William Cody; Herring, Matthew; Truong, Walter H. (The Journal of Knee Surgery, 2018)
The extensor mechanism of the knee—consisting of the four muscles of the quadriceps, the quadriceps tendon, the patella, and the patellar ligament—is essential for lower extremity function during both standing and ambulation. The presence of articular cartilage and growing physes in the pediatric knee, coupled with the generation of significant tensile force, creates an opportunity for pathology unique to the pediatric population.Tibial tubercle fractures and patella injuries are quite rare, and even pediatric-trained orthopaedic surgeons may not be exposed to these injuries on a regular basis. It is the intent of this article to discuss the current literature regarding the mechanism of injury, diagnostic workup, classification, indications for surgical versus non-surgical management, and techniques for operative management for both tibial tubercle and patella (transverse and sleeve) fractures.
Keywords: patella; tibial tubercle; fractures; pediatric; operative management